Adobe Analytics /? - Matisloff, Eric (For dummies)
Use Adobe Analytics as a marketer ?not a programmer!If you're a marketer in need of a non-technical, beginner's reference to using Adobe Analytics, this book is the perfect place to start. Adobe Analytics For Dummies arms you with a basic knowledge of